PENGGUNAAN APLIKASI E-PRINTS UNTUK PENGEMBANGAN INTITUTIONAL REPOSITORY DAN PENGARUHNYA TERHADAP PERINGKAT WEBOMETRICS PERGURUAN TINGGI DI INDONESIA - Ummi Rodliyah (Libraria: Jurnal Perpustakaan, 2016)
This article deals with the use of E-prints application to develop institutional repository and its influence on webometrics rank of universities in Indonesia. One of the indicators of success in the strategy of developing institutional repository in university libraries can be seen from its webometricsrank. Assessment in determining the rank of webometrics repository is based on some criteria, such as the level of visibility which is influenced by the software used. Based on this research, more than 50% of institutional repository in Indonesia use E-prints application, whileDspace is the second most used application in Indonesia. Even though Ganesha Digital Library (GDL) is created as national product, the users no longer use or even leave it for not being refined simultaneously by its developer. Some universities which used to apply GDL have immigrated to Eprints application, such as UIN SunanAmpel Surabaya and UIN SunanKalijaga Yogyakarta.